PREPARAÇÃO DE UM MATERIAL DE REFERÊNCIA IN HOUSE PARA Fe, Ca, Si, Ni, Na, P E V EM ELETRODOS DE CARBONO DA INDÚSTRIA DE ALUMÍNIO - Silva, Marcos Moura (2014)
The use of certified reference materials is an alternative that laboratories have to ensure the quality of their analyzes. Many laboratories have been investing in the production of their own reference materials in-house. This study presents the application of an interlaboratory test on the certification of Fe, Ca, Si, Ni, Na, P and V in a sample of carbon electrodes candidate reference material in-house, from an aluminum industry in Brazil. The sample was crushed, milled and quartered. Subsequently, the material was filled into 128 botlles. Homogeneity tests were conducted on material that testified that the material remained homogeneous after preparation and stable over time of study. The material certification was made through a collaborative program which included the participation of seven laboratories in different locations. After applying the Cochran and Grubbs tests the values provided by laboratories certified values in ppm were: 589.08 ± 25.28 for Fe, 142.89 ± 12.03 for Ca; 332.03 ± 20.55 to V, 178.07 ± 9.26 for Ni, 326.11 ± 24.07 for Na; 134.17 ± 6.59 for Si and 7.38 ± 1.97 for P. Finally, the laboratories were compared using the z-score test and was observed satisfactory performance, except for the the laboratory 1 for Si analysis, which showed discrepant deviation of the others. The application of variance analysis led to the conclusion that the material was homogeneous and stable enough to be used as a reference material for quality control procedure.